Routine measurement of plasma chromogranin B has limited clinical utility in the management of patients with neuroendocrine tumours. (24th December 2015) - Monaghan, P.J.; Lamarca, A.; Valle, J.W.; Hubner, R.A.; Mansoor, W.; Trainer, P.J.; Darby, D.
Summary: Objective: Chromogranin A (CgA) and B (CgB) are markers for monitoring disease status in patients with gastroenteropancreatic neuroendocrine tumours (NETs). These are specialized diagnostic tests often necessitating referral of specimens to a supraregional assay service (SAS) laboratory for analysis. The aim of this audit was to assess whether measurement of either plasma CgA or CgB alone provides sufficient clinical information in comparison with the current practice of measuring both markers together. Design: A retrospective analysis was undertaken for all chromogranin tests requested for patients with a known NET diagnosis. Results were categorized based on whether plasma concentrations were elevated for one or both CgA and CgB. Results: A total of 325 sequential patients with a NET diagnosis had plasma chromogranin levels measured during the period of review. Baseline CgA was elevated in 60·9% of patients. Isolated elevations in CgA (with normal CgB) were found in 44·9% of patients, whilst combined elevations in both CgA and CgB were found in 16% of patients. Combined CgA and CgB concentrations within the normal range were observed for 38·5% of patients. Only two patients (0·6%) had an isolated elevation in CgB at baseline. Both patients had a diagnosis of pancreatic NET and were radiologically stable. Plasma CgA and CgB corresponded with disease stage (localized vs metastatic). CgB in addition to CgA did not provide any significant improvement in diagnostic performance for identification of metastatic disease compared to CgA alone. Conclusions: Based on this NET population and specific assay performance characteristics, CgA alone provides sufficient information for the management of NET patients; the routine estimation of CgB in all patients is not informative in clinical practice.